Genomic regions associated with performance and carcass traits on chromosome 5 of Brazilian chicken lines - Silva, Fernanda Eliza de Jesus; Guido, Luiza Nicolosi; Gazaffi, Rodrigo; Garcia, Antonio Augusto Franco; Ledur, Mônica Corrêa; Coutinho, Luiz Lehmann; do Rosário, Millor Fernandes (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to genotype, construct the linkage map and map quantitative trait loci (QTL) associated with performance and carcass on chromosome 5 of Brazilian chickens lines. It was used a F2 CTCT chicken population, resulting from the crossing of males from a CC layer line with females from a TT broiler line. A total of 356 animals were genotyped with 11 microsatellite markers. Genotypic characterization was carried out by the estimation of the following genotypic parameters: polymorphic information content (0.45–0.69), observed (0.48–1.00) and expected (0.48–0.74) heterozygosities, and number of alleles per locus (3–5). QTL mapping used interval mapping combined with phenotypic modeling via mixed model. The length of the linkage map was 174.7 cM. No inversions were found between the obtained map, the consensus map, and the genome. Nine QTL were mapped, of which seven were suggestive (log of odds, LOD≤1.5) and two significant at the chromosome level (LOD>3.0). Six of these QTL are original: feed conversion and feed efficiency from 35 to 41 days of age (significative), weight of head and liver, and triglycerides and triglycerides+cholesterol. The CTCT population shows genotypic variability, the linkage map is similar to consensus map and genome, and new QTL were mapped.